PEMANTAUAN KEJADIAN BANJIR LAHAN SAWAH MENGGUNAKAN DATA PENGINDERAAN JAUH Moderate Resolution Imaging Spectroradiometer (MODIS) DI PROVINSI JAWA TIMUR DAN BALI - Zubaidah, Any; Dirgahayu, Dede; Pasaribu, Junita Monika (Jurnal Ilmiah Widya, 2013)
This paper discussed about the utilization of MODIS and TRMM satellite data to monitor flood in paddy field. The purpose of this research is to improve the quality of provision spatial information of flood prone area in the paddy field in East Java and Bali Province which can be done periodically (monthly) based on remote sensing data. Data used in this research is Terra/Aqua MODIS (Moderate Resolution Imaging Spectoradiometer) on November and December 2011 on 8 daily period, rainfall data which is obtained from TRMM data in the same period on November and December 2011, standard extensive field and administration map of East Java and Bali province. The method which is used in this research is to combine EVI (Enhance Vegetation Index) with rainfall data in the same period in order to obtain flood prone area, which is classified into 5 classes, namely non flood, mild, moderate, heavy, and very heavy.